Impact of medical-nursing combined policy pilot on hospitalization frequency of middle-aged and older patients with chronic diseases: a quasi-experimental study based on China Health and Retirement Longitudinal Study - Fan, Penghao; Li, Hongying; Xu, Hongyan; Rong, Chao (Frontiers in Public Health, 2024)
To address the growing burden of older adult care, the Chinese government has introduced a policy that integrates medical care with elder care, launching two batches of national pilot projects. A majority of the older adult population suffers from one or more chronic diseases, with many experiencing multiple chronic conditions, necessitating support from both elder care and medical services. Using panel data from the China Health and Retirement Longitudinal Study (CHARLS) spanning 2011 to 2020, this study employs the difference-in-difference (DID) model to analyze the impact of the integrated medical-nursing policy on the physical health of older patients with chronic diseases. The study found that the average annual number of hospitalizations for older individuals with one or more chronic diseases was 0.276. The integrated medical-nursing policy reduced hospitalizations by 0.0405. Additionally, the average annual hospitalization rate for older individuals with two or more chronic diseases was 0.339, higher than the former group. The integrated medical-nursing policy reduced hospitalizations by 0.0738 in this group. Therefore, the pilot study demonstrates that the implementation of the integrated medical-nursing policy has significantly improved the physical health of older patients with chronic diseases. The government should promote these policies on a larger scale, explore various forms of integrated medical care, and provide more comprehensive medical and elder care services for older patients with chronic diseases.